The effect of albumin and hemoglobin levels on the prognosis of early-stage cervical cancer: a prospective, single-center-based cohort study - Xinmei Wang; Juan Xu; Hongyuan Zhang; Pengpeng Qu (BMC, 2023)
Abstract Background Serum albumin (ALB) and hemoglobin (HGB) are important serum biochemical indices of the nutritional status of patients and are associated with cancer development. We investigated the relationship between ALB and HGB levels and clinicopathologic characteristics of early-stage cervical cancer to determine the influence of ALB and HGB on the prognosis of early-stage cervical cancer. Methods The clinical data of 560 patients with International Federation of Gynaecology and Obstetrics (FIGO, 2009) stage IA1-IIA2 cervical cancer from January 2005 to December 2010 were retrospectively analyzed. The relationship between serum ALB and HGB levels and clinicopathological characteristics of patients were analyzed. The patients were followed-up for 12-138 months. The effects of ALB and HGB levels on the prognosis were analyzed by Cox regression, log-rank test, and the Kaplan-Meier method. Results The rate of patients with pelvic lymph node metastasis (PLNM), tumor diameter ≥ 4 cm, lymphovascular space invasion (LVSI), and deep stromal invasion was significantly higher in the anemia and hypoalbuminemia group than in the normal group (P < 0.05). The progression-free survival (PFS) and overall survival (OS) of patients in the hypoalbuminemia group and anemia group were significantly lower than that of the normal group (P < 0.05). FIGO stage, tumor diameter, PLNM, depth of stromal invasion, LVSI, the levels of ALB and HGB were risk factors for the prognosis of cervical cancer patients (P < 0.05). Conclusion Patients with hypoproteinemia and anemia in early-stage cervical cancer are more likely to have higher tumor stage, larger tumor size, PLNM, LVSI, and deep stromal invasion. In addition, patients with hypoproteinemia and anemia have a poorer prognosis than those without the condition. Therefore, it is of great significance to detect the ALB and HGB levels of patients and improve the nutritional status of patients in a timely manner for better prognosis of cervical cancer.